Evaluación de mezclas asfálticas reciclables con aditivos: Una alternativa de reducción de impactos económicos y ambientales (2016)
This research project is a contribution, from an academic point of view, to the use of new asphalt mixtures aimed at solving priority needs in road network maintenance. Its main goal was the evaluation of four asphalt mixtures [MDC - 19], via the Marshall method, using recycled material from planed pavement [RAP] with variations in the content of the mixture. The pre-experimental stage included laboratory testing for the characterization of the components of the design mixes, in accordance with the standards set by the National Roads Institute; the experimental phase evaluated the mixture with regard to the dynamic module, the resistance to distortion due to fatigue and the adhesion. According to the results we determined that the optimum amount of asphalt increases according to the relation of RAP content in the mixture and there was evidence of an improvement of the same regarding resistance and distortion; moreover, the study validated as satisfactory the use of the rejuvenating additive material in the recycled RAP material which allows us to confirm that the additive significantly improved the conditions of the asphalt.